ANALISIS PERATAAN LABA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Pratiwi, Ni Wayan Piwi Indah; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Income smoothing is an action that deliberately done management to reduce fluctuations in reported earnings with various purposes for the company's performance looks stable and healthy. Income smoothing for shareholders wants the profit earned to remain stable and not to experience any significant fluctuations so that the desired target hold full confidence from the shareholders in making decision. Practice income smoothing in a company, it is important to know the factors that affect income smoothing. This study uses 6 factors that are expected to influence income smoothing, the six factors are company size, debt to equity ratio, institutional ownership, profitability, dividend payout ratio, firm value. The purpose of this study to determine the analysis of income smoothing and the factors that influence it. The research was conducted at Manufacturing company which listed in Bursa Efek Indonesia (BEI) year 2013-2015. The number of samples obtained as many as 132 research samples for 3 periods. Sample selection technique used is nonprobability sampling method that is purposive sampling technique. The eckel index is used as a distinguishing indicator of issuers between those who do and do not make income smoothing. Data analysis technique used in this research is multiple linear regression analysis. The result of analysis in this research shows that firm size, debt to equity ratio, institutional ownership, profitability, dividend payout ratio, firm value have positive effect to income smoothing. Keywords:   Income Smoothing, Company Size, Debt to Equity Ratio, Institutional Ownership, Profitability, Devidend Payout Ratio, Corporate Value